Strengthening Law Enforcement Against Digital Identity Abuse In Online Lending: A Normative And Forensic Analysis To Achieve Legal Certainty In Indonesia - Rachmat Hidayat, Afif; Latif , Abdul; Kristiawanto, Kristiawanto (Sahabat Publikasi, 2025)
The rapid expansion of digital financial services has transformed online lending into a mainstream financial solution, yet simultaneously created new vulnerabilities involving the misuse of digital identities. This study examines the legal enforcement mechanisms applied to perpetrators who unlawfully use another person's identity to obtain online loans within Indonesia's evolving cybercrime landscape. Employing a normative juridical method integrated with statutory, conceptual, and case-based approaches, this research analyzes the adequacy of existing regulations—including the Criminal Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law and their practical implementation. Findings reveal that regulatory fragmentation, insufficient verification standards, and limited digital forensic competence hinder effective prosecution. Case analyzes further demonstrate recurring issues in evidentiary quality, particularly concerning metadata integrity, digital traceability, and chain-of-custody compliance. These constraints contribute to uncertainty in determining liability, thereby undermining broader legal certainty. The study argues that strengthening legal enforcement requires a multi-dimensional strategy encompassing the adoption of specialized legislation on digital identity misuse, enhancement of forensic capabilities, mandatory biometric verification for fintech providers, and integrated inter-agency coordination through a national digital identity framework. This research contributes theoretically by advancing discourse on cybercrime and digital identity governance, and practically by offering policy recommendations to enhance legal certainty, accountability, and public trust in the digital financial ecosystem.